A Conceptual Framework of Social Communication: Clinical Applications to Pediatric Traumatic Brain Injury - Wiseman-Hakes, Catherine; Kakonge, Lisa; Doherty, Meghan; Beauchamp, Miriam (Seminars in Speech and Language, 2020)
Social communication impairments are common following pediatric traumatic brain injury (TBI) and can lead to social isolation, and poor social outcomes. Social communication has been documented as a persistent area of need in terms of proper assessment and intervention; however, this is not consistently addressed in clinical practice. While there is a body of evidence regarding social communication impairments and pediatric TBI, this area is not yet fully understood and remains underrecognized. To meet this gap, we provide a conceptual framework of social communication from a neurodevelopmental perspective, which can be applied to better understand the social communication impairments associated with pediatric TBI. We propose a general model of social communication with component constructs and consideration of internal factors such as sex and gender. These can inform considerations, clinical applications, and future research in assessment and evidence-based interventions within the domain of social communication.
Keywords: social communication; pediatrics; TBI; communication; pragmatics